Correlation of placental histopathology in fetal growth restriction with fetal outcome - Singh, Pratyusha; Pandher, Dilpreet Kaur; Goel, Poonam; Handa, Uma; Jain, Suksham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Fetal Growth Restriction (FGR), affecting 5-10% of pregnancies worldwide, is a significant cause of perinatal morbidity and mortality. The placenta plays a central role in the pathogenesis of FGR, with various histopathological abnormalities contributing to impaired fetal growth. Understanding the relationship between placental pathology and neonatal outcomes can guide clinical management and improve future pregnancy outcomes. This study aimed to find out the specific placental histopathologies present in FGR pregnancies and correlate them with the type and severity of FGR as well as neonatal outcome. Methods: An analytical cross-sectional study was conducted on 92 FGR pregnancies at Government Medical College, Chandigarh over 18 months. Placental samples were examined histologically, and findings were correlated with clinical data including doppler studies, birth weight, Apgar scores, NICU admission and neonatal mortality. Statistical analysis was performed using SPSS version 25.0, with significance set at p<0.05. Results: Early-onset FGR was observed in 36.9% and late-onset in 63.1% of cases. Placental histopathological analysis indicated that the most common abnormalities were syncytial knots (88%), fibrinoid necrosis (85.9%), and dystrophic calcifications (52.2%). Early-onset FGR was significantly associated with doppler abnormalities such as absent or reversed end-diastolic flow (AEDF/REDF) and poorer neonatal outcomes like low birth weight, low Apgar scores, higher NICU admissions (42.9%), and increased neonatal mortality (31.8%). Placental abnormalities detected in early-onset FGR includes massive peri villous fibrin deposition (MPVFD), chorioamnionitis, and diffuse dystrophic calcification. Conclusions: FGR is a complex condition with multifactorial etiology, often associated with multiple placental lesions. Placental abnormalities, particularly MPVFD, chorioamnionitis, diffuse dystrophic calcification are strongly associated with FGR severity and adverse neonatal outcomes. Routine placental histopathological examination in FGR cases provides valuable insights into its etiopathogenesis and optimizing fetal outcomes in subsequent pregnancies.